The Effect of Collocational Success on Essay Grading: A Case of Algerian EFL Learners - ARABET, Mohamed Akram (Journal of Human Sciences, 2019)
Collocations are an inherent and indispensable part of the language continuum. This work investigates the mastery of Verb+Noun lexical collocations by Algerian EFL learners at the University of Mentouri Brothers, Constantine 1. It is hypothesised that Algerian EFL learners have a low level of mastery in the usage and comprehension of Verb+Noun collocations. It is also hypothesised that the essays of Algerian EFL learners lack the use of appropriate Verb+Noun collocations, a factor that influences the grades they receive. An online corpus (BNC) and two other online websites (Collocation Checker & O.O.C.D) were used as tools to measure learners’ collocational competence. Examined collocations were extracted from the learners’ examination essays. The analysis was done manually through identification and corpus usage. The findings reveal that the Verb+Noun collocational errors that were spotted were not taken in consideration during the correction, even though they are an indispensable part that guarantees the use of correct language. The findings also confirm the aforementioned hypotheses, in addition to the fact that teachers are either unaware of the impact of collocations on the writing quality, or did not take them into account, because they did not teach them. This could be noted by the fact that even the essays that received the highest grades contain many collocational errors.